Ping Pong Game Implementation in C#: A Desktop Gaming Application - Razormist, Razormist (Journal Dekstop Application (JDA), 2025)
Ping Pong: The Game is a desktop-based educational project developed in the C# programming language to illustrate the practical application of programming principles through interactive game design. The project was created within the Visual Studio environment using the .NET Framework, emphasizing object-oriented and event-driven programming approaches. Its modular structure integrates several core components, including a game engine, AI controller, collision detection system, and real-time rendering module. Designed to merge entertainment and learning, the game enables users to explore algorithmic logic, graphical rendering, and artificial intelligence behavior in an accessible and engaging context. The implementation demonstrates stable performance, responsive controls, and accurate collision handling, providing a balanced gameplay experience against an AI opponent. Results indicate that the system effectively translates theoretical programming concepts into functional interaction, reinforcing learners’ comprehension of coding, logic structuring, and software architecture. Although limited to single-player mode and fixed AI difficulty, the project provides a strong foundation for future development such as multiplayer integration, dynamic difficulty scaling, and cross-platform deployment. Overall, Ping Pong: The Game exemplifies how simple, well-structured applications can serve as effective educational tools that bridge the gap between theoretical understanding and practical programming experience.